Modulation of Gut Microbiota by Essential Oils and Inorganic Nanoparticles: Impact in Nutrition and Health - Lazar, Veronica; Holban, Alina-Maria; Curutiu, Carmen; Ditu, Lia Mara (Frontiers in Nutrition, 2022)
Microbiota plays a crucial role in human health and disease; therefore, the modulation of this complex and yet widely unexplored ecosystem is a biomedical priority. Numerous antibacterial alternatives have been developed in recent years, imposed by the huge problem of antibioresistance, but also by the people demand for natural therapeutical products without side effects, as dysbiosis, cyto/hepatotoxicity. Current studies are focusing mainly in the development of nanoparticles (NPs) functionalized with herbal and fruit essential oils (EOs) to fight resistant pathogens. This is due to their increased efficiency against susceptible, multidrug resistant and biofilm embedded microorganisms. They are also studied because of their versatile properties, size and possibility to ensure a targeted administration and a controlled release of bioactive substances. Accordingly, an increasing number of studies addressing the effects of functional nanoparticles and plant products on microbial pathogens has been observed. Regardless the beneficial role of EOs and NPs in the treatment of infectious diseases, concerns regarding their potential activity against human microbiota raised constantly in recent years. The main focus of current research is on gut microbiota (GM) due to well documented metabolic and immunological functions of gut microbes. Moreover, GM is constantly exposed to micro- and nano-particles, but also plant products (including EOs). Because of the great diversity of both microbiota and chemical antimicrobial alternatives (i.e. nanomaterials and EOs), here we limit our discussion on the interactions of gut microbiota, inorganic NPs and EOs. Impact of accidental exposure caused by ingestion of day care products, foods, atmospheric particles and drugs containing nanoparticles and/or fruit EOs on gut dysbiosis and associated diseases is also dissected in this paper. Current models developed to investigate mechanisms of dysbiosis after exposure to NPs / EOs and perspectives for identifying factors driving EOs functionalized NPs dysbiosis are reviewed.